Design and implementation of highly efficient UPS charging system with single stage power factor correction using SEPIC converter. (2021) - Sivamani, D.; Ramkumar, R.; Nazar Ali, A.; Shyam, D.
Abstract: With the fast expanding utilization of intensity electronic hardware, dynamic force factor adjustment (PFC) has gotten essential for some kinds of intensity supplies in the market today. Uninterruptible Power Supplies (UPS) are broadly used to convey solid and excellent capacity to basic burdens under all lattice conditions. This paper proposes a high-recurrence secluded UPS framework for low force applications. The proposed framework comprises of a solitary stage AC-DC converter, SEPIC DC-DC converter, and a battery. The single-stage AC-DC converter gives galvanic segregation, input power factor remedy, and constant conduction of both information and yields current. The low battery bank voltage is ventured up to high DC-interface voltage by utilizing a high voltage gain SEPIC converter. In this paper, UPS charging system with almost unity power factor is proposed. In conventional systems, the bridge rectifier and DC-DC converter are used in this system. Using this methodology, the power factor and harmonics are decreased. We use the bridgeless SEPIC converter for battery charging applications. This system can perform rectification and DC to DC conversion stages with improved power factor and low harmonics. Current control method (MOSFET) is used for control logic. Design of the converter is done in MATLAB and analysed the PI controller with optimized Kp, Ki using GA intelligent control method.